Convective drying kinetics of squash epicarp of cucurbita maxima and its uses in developing gluten-free bread (2022)
This study was conducted to obtain semi-empirical mathematical models that represent the convective drying kinetics of squash epicarp at different temperatures (55, 65 and 75°C/10% RH/ drying speed 1ms-1). The best drying condition was selected to obtain flour, which was then characterized and used for the preparation of gluten-free bread. Subsequently, the effect of incorporating squash epicarp flour (SEF) into 4 levels (0-control, 15, 20 and 25g / 100 g of flour) on the sensory acceptance of the bread was evaluated. The results of this study are that the two-term model best describes the curve obtained at 55 °C, and the logarithmic model best describes the curves obtained at 65 °C and 75 °C. The temperature of 65 °C was selected as the best drying condition. Finally, the highest acceptance and purchase intention was obtained from the bread produced with 15 g SEF / 100 g of flour.